Perancangan Design UI/UX Aplikasi CouPal Menggunakan Metode Design Thinking Sebagai Sarana Edukasi Pasangan Membangun Good Relationship Dalam Menghadapi Tantangan Pernikahan - Maulidiya, Bellina (Program Studi Informatika Fakultas Teknik Universitas Janabadra, 2024)
Mobile applications have become an important platform in everyday life, including in the dynamics of interpersonal relationships, especially in romantic relationships. However, unhealthy conditions often arise in these relationships, or better known as toxic relationships, which can have a negative impact on a person's mental health. Statistical data shows an increase in cases of dating violence, domestic violence (KDRT), and divorce in Indonesia. This data indicates the couple's lack of readiness to establish a good relationship. Lack of information regarding the basics of marriage is one of the main causes of this problem. Therefore, CouPal is here as an innovative solution by providing the first relationship psychoeducation application in Indonesia. Through integrated UI/UX design, CouPal aims to help couples understand and improve the quality of relationships, resolve conflicts, understand the role of family education in reducing violence or conflict in the household, and reduce divorce rates. This application also provides online consultation services with couple psychologists and family psychologists. CouPal UI/UX design test results show a high level of user satisfaction, which was achieved through the application of the design thinking method. Keywords: UI/UX, Good Relationship, Psychoeducation, Design Thinking.